2014
DOI: 10.3171/2014.5.peds12614
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cervicomedullary cord compression and alterations in cerebrospinal fluid dynamics in children with achondroplasia: review of an 11-year surgical case series

Abstract: Object Achondroplasia may be associated with compression at the cervicomedullary junction. Determining which patients are at greatest risk for neurological complications of cervicomedullary compression can be difficult. In the current study the authors reviewed their records to determine the incidence and clinical significance of dynamic cervicomedullary stenosis and obstruction of CSF flow along with surgical outcomes following posterior fossa decompression. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Better visualization of neural tissue is forthcoming, but usually sedation or general anesthesia will be needed because of the length of the procedure. Often multiposition MRI is elected [126, 129]. Flow studies may be of some help as well in determining whether surgical intervention is warranted [126, 128].…”
Section: Natural History and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Better visualization of neural tissue is forthcoming, but usually sedation or general anesthesia will be needed because of the length of the procedure. Often multiposition MRI is elected [126, 129]. Flow studies may be of some help as well in determining whether surgical intervention is warranted [126, 128].…”
Section: Natural History and Managementmentioning
confidence: 99%
“…Although this is likely the most important mechanism, there is also evidence that obliteration of cerebrospinal fluid flow at the craniocervical junction may be a factor in development of hydrocephalus, too [128, 129, 201, 202]. It is not unreasonable to posit that there are two distinct processes that can give rise to increased intracranial pressure in those with achondroplasia.…”
Section: Natural History and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…This was managed by adding instrumented fusion with cross-links to maintain distance between the paraspinal muscles and the cord. dMRI studies in achondroplasia and rheumatoid arthritis patients have shown increased risk of dynamic compression at the cervico-medullary junction [ 37 38 39 ]. Dynamic imaging has also proven to be useful in children with skeletal dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, spinal cord and cauda equina compression related to thoracolumbar stenosis are more prominent in adolescence or adulthood . Early cervicomedullary decompression leads to neurological and developmental improvement, although mortality and morbidity remain worth considering and indications for surgical treatment are still debated . Indeed, a close neurological and neuroradiological follow‐up is often necessary from the first months of life.…”
mentioning
confidence: 99%